Seed bury vs broadcast in direct seeding: their effects on the germination of different woody plant species, in a degraded semi-arid area, Southern Ethiopia - Shiferaw Alem (Brawijaya University, 2020)
Direct seeding is considered as an option for afforestation programs to rehabilitate degraded lands. However, scant knowledge is available on the effect of seed sowing techniques on the germination of different woody plants in a semi-arid degraded area. Therefore, the objectives of this study paper are 1) to evaluate the effects of broadcasting vs seed bury on the germination of 15 different woody plant species in a degraded semi-arid area 2) to select woody plants that can result in higher germination percent in the field for restoration projects. To achieve the objectives, a study was carried out in the field, with a randomized complete block design (RCBD). One-way ANOVA, t-test and descriptive statistics were used to analyze the data. The result indicated that the average germination percent for buried and broadcasted seeds were 18.1% and 5.2%, respectively. Among the broadcasted species seeds, Schinus molle achieved the highest germination (23.3%) while Terminalia browni achieved the lowest germination (0.25%). Among the different species seeds that were buried, Dolanix regia achieved the lowest germination (1.5%) while Sesbania sesban resulted in the highest germination (64%). The t-test result revealed a significant difference in the mean germination of the broadcasted and buried seeds (p<0.05). The ANOVA result also revealed significant differences in the germination of the different families of the species. For most of the studied species (86%), seed bury has resulted in higher germination percent relative to the broadcasted seeds. Therefore, it is recommended that in semi-arid degraded land, it could be better to apply seed bury than the broadcasting when there is an objective to use direct seeding for afforestation.